Quantitative Analysis of Dynamic Subacromial Ultrasonography: Reliability and Influencing Factors - Lin, Che-Yu; Chou, Chia-Ching; Chen, Lan-Rong; Wu, Wei-Ting; Hsu, Po-Cheng; Yang, Tung-Han; Chang, Ke-Vin (Frontiers in Bioengineering and Biotechnology, 2022)
Objective Current imaging methods used to examine patients with subacromial impingement syndrome (SIS) are limited by their semi-quantitative nature and their capability of capturing dynamic movements. This study aimed to develop a quantitative analytic model to assess subacromial motions using dynamic ultrasound and to examine their reliability and potential influencing factors. Method We included 48 healthy volunteers and examined their subacromial motions with dynamic ultrasound imaging. The parameters were the minimal vertical acromiohumeral distance, rotation radius, and degrees of the humeral head. The generalized estimating equation (GEE) was used to investigate the impact of different shoulder laterality, postures, and motion phases on the outcome. Result Using the data of the minimal vertical acromiohumeral distance, the intra-rater and inter-rater reliabilities (intra-class correlation coefficient) were determined as 0.94 and 0.88, respectively. In the GEE analysis, a decrease in the minimal vertical acromiohumeral distance was associated with the abduction phase and full-can posture, with a beta coefficient of -0.02 cm (95% confidence interval [CI], -0.03 to -0.01) and -0.07 cm (95% CI, -0.11 to -0.02), respectively. The abduction phase led to a decrease in the radius of humeral rotation and an increase in the angle of humeral rotation, with a beta coefficient of -1.28 cm (95% CI, -2.16 to -0.40) and 6.60° (95% CI, 3.54 to 9.67), respectively. A significant negative correlation was observed between the rotation angle and radius of the humeral head and between the rotation angle and the minimal vertical acromiohumeral distance. Conclusion Quantitative analysis of dynamic ultrasound imaging enables the delineation of subacromial motion with good reliability. The vertical acromiohumeral distance is the lowest in the abduction phase and full-can posture, and the rotation angle of the humeral head has the potential to serve as a new parameter for the evaluation of SIS.